Anti-thrombosis Effects and Mechanisms by Xueshuantong Capsule Under Different Flow Conditions - Shuxian Han; Ying Chen; Jinyu Wang; Qian Zhang; Bing Han; Yimeng Ge; Yanhua Xiang; Rixin Liang; Xiaoxin Zhu; Yun You; Fulong Liao (Frontiers Media S.A., 2019)
Xueshuantong capsule (XST) is a patented traditional Chinese medicine used for the prevention and treatment of thrombosis. The molecular mechanism of anti-thrombotic effect of XST was investigated through the cross-talk among the platelets/leukocytes, endothelial cells (ECs), and flow shear stress. The Bioflux 1000 system was used to generate two levels of shear stress conditions: 0.1 and 0.9 Pa. Bioflux Metamorph microscopic imaging system was used to analyze the adhesion cell numbers. Protein expressions were detected by western blotting and flow cytometry. The flow-cytometry results showed that under 0.1 Pa flow, XST decreased ADP induced platelets CD62p surface expression in a concentration-dependent manner. Under 0.9 Pa flow, XST at a concentration of 0.15 g⋅L-1 reduced the platelets activation by 29.5%, and aspirin (ASA) showed no inhibitory effects. XST showed similar efficiency on monocytes adhesion both under 0.1 and 0.9 Pa flow conditions, and the inhibition rate was 30.2 and 28.3%, respectively. Under 0.9 Pa flow, the anti-adhesive effects of XST might be associated with the suppression of VE-cadherin and Cx43 in HUVECs. Blood flow not only acts as a drug transporter, but also exerts its effects to influence the pharmacodynamics of XST. Effects of XST on inhibiting platelets activation and suppressing platelets/leukocytes adhesion to injured ECs are not only concentration-dependent, but also shear stress-dependent. The mechanic forces combined with traditional Chinese medicine may be used as a precise treatment for cardiovascular diseases.